Using public procurement as a decarbonisation policy: A look at Germany - Olga Chiappinelli; Vera Zipperer (DIW Economic Bulletin, 2017)
Public authorities spend large proportions of their GDP on goods and services and are therefore responsible for a significant share of embedded emissions. Given this large impact, governments have the responsibility of decarbonizing their purchases, as well as the potential to influence markets towards sustainability. So-called 'Green Public Procurement' (GPP) consists in the use of environmental criteria in the procurement process. In Germany, Europe's biggest economy, public purchases account for 15 percent of annual GDP. However, despite a rising trend, the use of GPP in public procurement contracts remains marginal. The main barriers to broader implementation is the perception that including environmental criteria leads to higher procurement costs. Further, administrative capacity faces constraints to acquire legal and technical expertise about GPP. A clear political mandate for financing the incremental costs incurred from the environmental impact of procured goods and services, as well as specific training programs for procurement officials can encourage an increased adoption of GPP in the future.
Keywords: H50; H57; Q58; 330; green public procurement; government spending; carbon footprint; environmental policies